The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.braindev.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Ictal EEG patterns in epilepsy with centro-temporal spikes

Abstract: Purpose: To describe the EEG pattern of seizures in patients with benign childhood epilepsy with centro-temporal spikes (BCECTS). Methods: The clinical and EEG data of 701 BCECTS patients with at least a 3 years follow-up were reviewed from 10 epilepsy centers. Results: Thirty-four seizures were recorded in 30 patients. Four different ictal EEG patterns (A-D) were identified. The most frequent (pattern A) was characterized by low voltage activity of fast rhythmic spikes, increasing in amplitude and decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…In addition, a study combining EEG source imaging and fMRI showed propagation of the interictal activity from the rolandic region corresponding to the hand and face area, to the operculum and insula [11] . It has been previously suggested that involvement of insula likely explains the sensations of laryngeal constriction and choking that is often reported by patients with self-limited epilepsy with centrotemporal spikes [3] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study combining EEG source imaging and fMRI showed propagation of the interictal activity from the rolandic region corresponding to the hand and face area, to the operculum and insula [11] . It has been previously suggested that involvement of insula likely explains the sensations of laryngeal constriction and choking that is often reported by patients with self-limited epilepsy with centrotemporal spikes [3] .…”
Section: Discussionmentioning
confidence: 99%
“…The largest number of patients was reported by Capovilla and co-workers [3] . They retrospectively collected 30 patients with ictal recordings, and they identified four types of ictal patterns, the most common being the low-voltage fast activity.…”
Section: Introductionmentioning
confidence: 94%
“…Rolandic epilepsy (RE) or benign childhood epilepsy with centro‐temporal spikes is the most common childhood focal epilepsy (Fejerman, ; Panayiotopoulos et al ., ), usually starting between 7 and 10 years. The cardinal features are focal seizures consisting of unilateral facial sensory‐motor symptoms, oropharyngo‐laryngeal symptoms, speech arrest, and hypersalivation (Capovilla et al ., ). Centro‐temporal spikes, typically activated by drowsiness and slow sleep, indicate that the epileptogenic zone in Rolandic epilepsy involves neuronal networks within the Rolandic cortex surrounding the central fissure bilaterally.…”
Section: Involvement Of Autonomic Sensorimotor Auditory Vocal Andmentioning
confidence: 97%
“…In 1990, Gutierrez et al described an ictal event with speech arrest only characterized by a short train of ictal alpha activity, and then two multiple spikes and wave complexes originated from the left centrotemporal region followed by marked attenuation of the left hemispheric background [115]. Subclinical rhythmic discharges of spike and wave in the centrotemporal region have been documented by several authors in RE [116,117]. Saint-Martin et al in 2001 described a series of patients presenting with typical and also atypical ictal manifestations such as falls, negative myoclonus and observed that positive motor phenomenon correlated to the spike component preceding a negative motor phenomenon, correlated with the slow-wave component of the spike and wave complex [118].…”
Section: Ictal Eegmentioning
confidence: 99%
“…Capovilla et al recorded 34 seizures in 30 patients with RE and described four electrographic seizure patterns thus emphasizing that ictal pattern for RE is not unique [116]:…”
Section: Ictal Eegmentioning
confidence: 99%